2016
DOI: 10.18632/oncotarget.13855
|View full text |Cite
|
Sign up to set email alerts
|

Tumor compactness improves the preoperative volumetry-based prediction of the pathological complete response of rectal cancer after preoperative concurrent chemoradiotherapy

Abstract: In addition to clinical factors (tumor and node stage) and treatment factors (equivalent radiotherapy dose and chemotherapy regimen), we assessed whether different performances of various tumor volume measurements help predict the pathological complete response (pCR) of locally advanced rectal cancer (LARC) after preoperative concurrent chemoradiotherapy (CCRT). A total of 122 patients with LARC treated with a long course of CCRT, between December 2009 and March 2015, were enrolled in this bi-institutional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(64 reference statements)
2
12
0
1
Order By: Relevance
“…Parameters of tumor position, tumor circumferential percentage, patient's age and gender were not significantly correlated with pCR in the study, which was consistent with previously published data [ 24 , 34 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Parameters of tumor position, tumor circumferential percentage, patient's age and gender were not significantly correlated with pCR in the study, which was consistent with previously published data [ 24 , 34 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we analyzed correlations between the no/low response status of CCRT and RTV, ATV, respectively, and found that ATV could not be used as an independent predictor to predict the patient's resistance to CCRT, while RTV could. In previous studies, Chen et al [43] found that GTV(actually ATV) was negatively correlated with the prognosis of patients with esophageal cancer after definitive radiotherapy, and numerous studies [22,44,45] on preoperative CCRT for rectal cancer have shown that tumor volume was negatively correlated with the pCR status after preoperative CCRT. Although the…”
Section: Discussionmentioning
confidence: 98%
“…Indirect image parameters are obtained through the contraction and enlargement function of Pinnacle software, as shown in Fig 1, including real tumor volume (RTV), tumor surface area inner the intestine(TSAI), tumor surface area outside the intestine (TSAO), total surface area (TSA) and tumor compactness (TC). It should be noted that TC is a secondary derivative parameter, which can be calculated from the following equation [22][23][24], tumor compactness ¼ real tumor volume total surface area 1:5 . The red line encompasses the approximate tumor volume (ATV).…”
Section: Volumetric Imaging Parametersmentioning
confidence: 99%
“…Multivariate logistic regression analysis revealed tumor compactness ( P = .001) as significant predictor of a pCR. In addition, poor tumor compactness was closely associated with lymphovascular space invasion ( P = .008) and pathological nodal status ( P = .003) . Tumor radiomic signature, such as sphericity and compactness, is a radiomic factor and is often considered to be associated with tumor invasiveness and morphology, which are affected by stabilizing mechanical forces and three‐dimensional diffusion gradients .…”
Section: Discussionmentioning
confidence: 99%